Origins of lithium inventory reversibility with an alloying functional layer in anode-free lithium metal batteries - Lennart Wichmann; Shi-Kai Jiang; Johannes Helmut Thienenkamp; Marvin Mohrhardt; Bing Joe Hwang; Martin Winter; Gunther Brunklaus (Nature Communications)
Abstract Alloying coatings are widely accepted to boost the reversibility of lithium inventory in anode-free cell configurations. While diminished capacity losses are evident from electrochemical data, their impact beyond decreasing the nucleation overpotential remains elusive. Herein, in situ 7Li NMR spectroscopy is applied to differentiate capacity losses in pouch cells with representative electrochemical behavior. Next to an accelerated interphase formation, the alloying layer diminishes the formation of dead lithium deposits notably. In contrast to previous reports, the capacity lost to electronically insulated lithium deposits is not related to their tortuosity and surface area. Though alloy formation reduces the nucleation overpotential with coated copper, deconvolution of 7Li NMR spectra as well as scanning electron microscopy evidence predominantly compact lithium deposits in the initial cycles and a similar increase of high-surface area morphologies with bare and coated copper negative electrodes. Instead of improved lithium deposit morphology, the enhanced reversibility with the alloying layer is bestowed by improved interfacial transport towards the end of lithium dissolution. These insights add to the mechanistic understanding of dead lithium formation, exploiting impedance spectroscopy in the discharged state as a valuable tool to assess the ability to dissolve lithium metal from a given substrate.